An Analysis On Figurative Language Used In Emily Dickinson's Poems - Hidayanto, Habibi Nur (2004)
This study is about An Analysis on Figurative Language in Emily Dickinson's poems. The objectives of this study are (1) to find out the figurative language mainly used in Emily Dickinson's poems, (2) to find out the meaning of figurative language in Emily Dickinson's poems. The study uses a documentary data source that is primary sources. The primary sources are the text of poems itself: We Like March, Death Sets a Thing, Grass, Wild Nights, My Letter to the World, There Is a Certain Slant of Light, and Hope Is the Thing with Feathers taken from internet in Emily Dickinson's poems at www.yahoo.com. The methods of the data are collection, observation, and documentation. Based on the research, the writer concludes that after analyzing the data, Emily Dickinson's poems are using some figurative speech. They are: simile, apostrophe, personification, paradox, metonymy, synecdoche, hyperbole, and symbol. In addition, the dominant figurative language that Emily Dickinson used in her poems is apostrophe. Emily Dickinson's poems bring emotional feeling to the readers especially to penetrate into religion, friendship, and heroism.